Radiofrequency ablation compared to surgical resection for curative treatment of patients with colorectal liver metastases – a meta-analysis - van Amerongen, Martinus J.; Jenniskens, Sjoerd F.M.; van den Boezem, Peter B.; Fütterer, Jurgen J.; de Wilt, Johannes H.W. (HPB (Oxford, England), 2017)
Hepatic resection and ablative treatments, such as RFA are available treatment options for liver tumors. Advantages and disadvantages of these treatment options in patients with colorectal liver metastases need further evaluation. The purpose of this study was to systematically evaluate the role of radiofrequency ablation (RFA) compared to surgery in the curative treatment of patients with colorectal liver metastases (CRLM). A systematic search was performed from MEDLINE, EMBASE and the Cochrane Library for studies directly comparing RFA with resection for CRLM, after which variables were evaluated. RFA had significantly lower complication rates (OR = 0.44, 95% CI = 0.26–0.75, P = 0.002) compared to resection. However, RFA showed a higher rate of any recurrence (OR = 1.66, 95% CI = 1.15–2.40, P = 0.007), local recurrence (OR = 9.56, 95% CI = 6.85–13.35, P = 0.001), intrahepatic recurrence (OR = 1.96, 95% CI = 1.34–2.87, P = 0.001) and extrahepatic recurrence (OR = 1.21, 95% CI = 0.90–1.63, P = 0.22). Also, 5-year disease-free survival (OR = 2.20, 95% CI = 1.28–3.79, P = 0.005) and overall survival (OR = 2.35, 95% CI = 1.49–3.69, P = 0.001) were significantly lower in patients treated with RFA. RFA showed a significantly lower rate of complications, but also a lower survival and a higher rate of recurrence as compared to surgical resection. All the included studies were subject to possible patient selection bias and therefore randomized clinical trials are needed to accurately evaluate these treatment modalities.